Search for W' → tb decays in the hadronic final state using pp collisions at √s = 13 TeV with the ATLAS detector - Alconada Verzini, María Josefina (2018)
A search for W'-boson production in the W′→t<mover accent="true" is="true">b¯</mover>→q<mover accent="true" is="true">q¯</mover>′b<mover accent="true" is="true">b¯</mover> decay channel is presented using 36.1 fb-1 of 13 TeV proton–proton collision data collected by the ATLAS detector at the Large Hadron Collider in 2015 and 2016. The search is interpreted in terms of both a left-handed and a right-handed chiral boson within the mass range 1–5 TeV. Identification of the hadronically decaying top quark is performed using jet substructure tagging techniques based on a shower deconstruction algorithm. No significant deviation from the Standard Model prediction is observed and the results are expressed as upper limits on the W′→t<mover accent="true" is="true">b¯</mover> production cross-section times branching ratio as a function of the W'-boson mass. These limits exclude W' bosons with right-handed couplings with masses below 3.0 TeV and W' bosons with left-handed couplings with masses below 2.9 TeV, at the 95% confidence level.